2021
DOI: 10.21203/rs.3.rs-1057169/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Piezo1 Promoted Hepatocellular Carcinoma Progression and EMT Through Activating TGF-β Signaling by Recruiting Rab5c

Abstract: Background Piezo1 plays critical roles in vascular development during early embryogenesis. However, the function of Piezo1 in hepatocellular carcinoma (HCC) remain elusive. This study aimed to explore the function and mechanisms of Piezo1 in HCC. Methods qRT-PCR, western blot and immunohistochemistry analyses were used to determine Piezo1 expression in HCC samples and cell lines. The clinical significance of Piezo1 was assessed in two independent study cohorts containing 280 patients with HCC. Gene set enric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Previous studies have shown that RAB5C is involved in tumorigenesis by promoting tumor cell migration [48]. We found that the expression of RAB5C was increased in CRC tumor tissues, which is consistent with previous studies which showed the increased expression of RAB5C in tumor tissues [48,49]. Interestingly, the expression level of RAB5C was positively correlated with BCAR4.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that RAB5C is involved in tumorigenesis by promoting tumor cell migration [48]. We found that the expression of RAB5C was increased in CRC tumor tissues, which is consistent with previous studies which showed the increased expression of RAB5C in tumor tissues [48,49]. Interestingly, the expression level of RAB5C was positively correlated with BCAR4.…”
Section: Discussionsupporting
confidence: 92%